U.S. nuclear weapons policy - Ferguson, Charles D; Perry, William James 1927-; Scowcroft, Brent; Council on Foreign Relations (New York Council on Foreign Relations, 2009)
The report notes that in the near term nuclear weapons will remain a fundamental element of U.S. national security. For this reason it emphasizes the importance of maintaining a safe, secure, and reliable deterrent nuclear force and makes recommendations on this front. The report also offers measures to advance important goals such as preventing nuclear terrorism and bolstering the nuclear nonproliferation regime--Foreword
Includes bibliographical references (p. 101-106)
1
Keywords: National security -- United States; Nuclear disarmament -- United States; Nuclear nonproliferation -- United States; Nuclear weapons -- Government policy -- United States; Kernwaffe; Rüstungspolitik; USA